UNINTENTIONAL INJURY MORTALITY IN INDIA, 2005: NATIONALLY REPRESENTATIVE MORTALITY SURVEY OF 1.1 MILLION HOMES. (7th October 2012) - Jagnoor, J; Suraweera, W; Keay, L; Ivers, R; Thakur, J, S; Jha,, P
Abstract : Background: Unintentional injuries are an important cause of death in India. However, no reliable nationally representative estimates of unintentional injury deaths are available. Aim: To estimate total unintentional injury mortality in India using results from a nationally representative survey of the causes of deaths. Methods: Unintentional injury deaths were examined in a nationally representative mortality survey covering 123 000 deaths occurring in 1.1 million homes. Trained non-medical field staff to interview all households in which a death had occurred from 2001 to 2003 within its Sample Registration System. Structured field reports detailing the events preceding death were obtained from living relatives of the deceased and emailed to two of 130 trained physicians who independently assigned an underlying cause to each death. Cause specific mortality proportions were applied to all-cause mortality estimates from the United Nations for the year 2005. Results: In the year 2005, unintentional injury caused 648 000 deaths (7% of all deaths; 58/100 000 population). Mortality rates were higher among males than females, and in rural versus urban areas. Road traffic injuries (185 000 deaths; 29% of unintentional injury deaths), falls (160 000 deaths, 25%) and drowning (73 000 deaths, 11%) were the three leading causes of unintentional injury mortality. The highest unintentional mortality rates were in those aged 70 years or older (410/100 000) mostly due to falls.